PATH FIT 1: movement enhancement - Escueta, Margaret M. (Manila : Edric Publishing House, 2024)
"Physical education (PE) plays a crucial role in the holistic development of individuals, particularly for students in educational settings. Here are some of the key reasons why physical education is important: 1) physical health; 2) mental health; 3) skill development; 4) social skills; 5) self-discipline and goal setting; 6) healthy lifestyle habits; 7) stress relief; 8) improved academic performance; 9) inclusivity and accessibility; and 10) encouraging lifelong physical activity."
Includes bibliography.
English.
Keywords: Physical fitness; Physical education